Combining humic acid with NPK fertilizer improved growth and yield of chili pepper in dry season - Ichwan, Budiyati; Eliyanti, Eliyanti; Irianto, Irianto; Zulkarnain, Zulkarnain (Advances in Horticultural Science, 2022)
This research aimed to study the effect of humic acid and NPK fertilizer (15:15:15) on growth and yield of red chili, and to obtain the most suitable composition of humic acid and NPK fertilizer which gave the best growth and yield. The study used a randomized block design with five replications. The treatments tested were the composition of humic acid and NPK fertilizer: 100% humic acid; 75% humic acid + 25% NPK; 50% humic acid + 50% NPK; 25% humic acid + 75% NPK; and 100% NPK. Data on plant growth and yield were processed by Analysis of Variance, and means were compared using Fisher’s Least Significant Difference test. In addition, data on plant biochemical and soil chemical parameters were determined compositely by mixing leaves taken from sample plants or soil samples into one homogenous sample. Results showed that there was no significant difference in growth and yield of plants treated with 100% humic acid in comparison with those plants treated with 100% NPK. However, in comparison with 100% humic acid, the application of different ratios of humic acid/NPK increased plant chlorophyll contents by 65% - 82% and total sugar by 28% - 71%. The application of humic acid/NPK increased soil fertility by improving soil pH as well as N, P and K. In the combination of humic acid/NPK, the best growth and yield were obtained with the application of 25% humic acid + 75% NPK fertilizers. Therefore, for the sustainability of chili cultivation, the use of humic acid needs to be accompanied with NPK fertilizers at a reduced amount, along with the increase in the dose of humic acid.